“Society at Large Is Heteronomous”: Cornelius Castoriadis and the Poietic Creation - Lombardinilo, Andrea (Italian Sociological Review, 2025)
Why is society at large heteronomous? How can imagination cope with the heteronomous drifts of social dynamics? Castoriadis’ theory of the imaginary construction of society provides some insightful reflections that allow a better understanding of how the “poietic” works in our hyperconnected society and how the “functional” impacts on the construction of society through the stifling and channelling of imagination. The aim of this paper is to theoretically investigate Castoriadis’ emphasis on the “pulsating process” that turns “instituting” societies into “instituted” ones through the power of symbolic and creative pathways, focusing on the conference Imaginary and Imagination at the Crossroads (1996). This paper emphasizes not only Castoriadis’ connection to the sociology of the arts and culture (from Vico to Becker, through Pareto, Adorno and Bourdieu), but also delves into his criticism on contemporary art, in line with denunciation of the “subversion of simulacrum” stigmatized by Jean Baudrillard in reference to the “conspiracy of art”. To the fore is the attempt to interpret the “loss of meaning” boosted by hyper-connectivity and permanent reproducibility of symbols, signs and contents, in a time of short-comings between the functional and poietic within the intramundane praxis of social and communicative acting, as Jürgen Habermas has recently pointed out.